Penerapan Hukum Terhadap Tindak Pidana Pembunuhan Dengan Sengaja Merampas Nyawa Orang Lain (Studi Kasus Nomor Putusan 616/Pid.B/2015/PN. Lbp) - Martinus Halawa; Zaini Munawir; Sri Hidayani (JUNCTO: Jurnal Ilmiah Hukum, 2020)
A fact that in the association of human life, individuals and groups, there are often deviations from the norms of his life, especially known legal norms. Where in mutual human association, this deviation of legal norms is referred to as a criminal offense. In recent years there has been more and more crime against human souls in society. The research method used in this study is the Library Research and Field Research. Judge's consideration or Ratio Decidendi is an argument or reason used by the judge as a legal consideration that becomes the basis before deciding a case. In practice before this juridical consideration is proven, the judge will first withdraw the facts in the trial that arises and constitute the cumulative conclusions of the witnesses' statements, the defendant's statements, and the evidence. The application of the law in this case to the murder case is legitimate while in reasonable terms because the application of the law must be in accordance with what was done by the perpetrators because the deterrent effect that is expected in the application of this law is very important.